Gender-related features of psychophysiological indicators in young basketball players - Boychenko , N.; Romanenko , V.; Tropin , Yu.; Pomeshchikova , I.; Chucha , N. (Sportyvnyi Visnyk Prydniprovia, 2025)
Introduction. Psychophysiological indicators are important factors in the effectiveness of competitive sports, comprehensively reflecting the functional state of athletes’bodies and ensuring the successful execution of technical and tactical actions. Research into the psychophysiological characteristics of young basketball players depending on gender, playing position, and match results has attracted the attention of many researchers. The purpose of the study is to determine the characteristics of psychophysiological indicators of young basketball players of different genders. Materials and methods of the study. The study involved 30 athletes (15 girls and 15 boys) aged 13-15 years who had 3-4 years of training experience. To assess the psychophysiological state, a set of instrumental tests was used, including assessment of reaction to a moving object, spatial perception, short-term visual memory, choice reaction, and differentiation reaction. The results of the study showed that for most of the parameters studied (sensory-motor reaction time, spatial perception, memory, choice reaction), no statistically significant gender differences were found. This indicates a similar level of development of cognitive and sensorimotor functions in boys and girls of this age, which is probably due to the influence of similar tasks in the training process. At the same time, the Go/No-Go test revealed a significant advantage for boys in differentiation reaction speed, which may be associated with greater motor activity and functional asymmetry of the cerebral cortex. The data obtained are consistent with previous studies. The data obtained are consistent with previous studies in the field of children’s and youth sports, which confirm the importance of an individual approach to training, taking into account neurophysiological characteristics. Conclusions. Gender differences in the psychophysiological indicators of young basketball players have been identified. The results show that gender differences are statistically insignificant for most psychophysiological indicators of young basketball players. The only significant difference was recorded in the Reaction Go/No-Go test, where boys demonstrated a higher reaction differentiation speed. This may indicate more effective regulation of nervous processes in males. In general, in adolescence (13–15 years), psychophysiological functions develop in parallel, and the level of complex reactions and cognitive skills is formed mainly under the influence of sports training, rather than gender.